2011
DOI: 10.1186/1471-2164-12-605
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-mediated gene regulation plays a minor role in the transcriptomic plasticity of cold-acclimated Zebrafish brain tissue

Abstract: BackgroundMicroRNAs (miRNAs) play important roles in regulating the expression of protein-coding genes by directing the degradation and/or repression of the translation of gene transcripts. Growing evidence shows that miRNAs are indispensable player in organismal development with its regulatory role in the growth and differentiation of cell lineages. However, the roles of miRNA-mediated regulation in environmental adaptation of organisms are largely unknown. To examine this potential regulatory capability, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 73 publications
(76 reference statements)
2
22
1
Order By: Relevance
“…However, Yang et al previously reported that cold acclimation trigger changes in some miRNA profiles in adult zebrafish brains and those miRNAs have poor associations to the affected genes. They concluded that microRNAs play a minor role in mediating transcriptome plasticity during cold stress [30]. It appears to be contradictory to our finding that the affected miRNAs have predicted target genes involved in cold-inducible biological processes, including melanogenesis, GnRH signaling pathway and circadian rhythm.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…However, Yang et al previously reported that cold acclimation trigger changes in some miRNA profiles in adult zebrafish brains and those miRNAs have poor associations to the affected genes. They concluded that microRNAs play a minor role in mediating transcriptome plasticity during cold stress [30]. It appears to be contradictory to our finding that the affected miRNAs have predicted target genes involved in cold-inducible biological processes, including melanogenesis, GnRH signaling pathway and circadian rhythm.…”
Section: Discussioncontrasting
confidence: 99%
“…As miRNAs accumulate over time, miRNAs exert their suppressive effect on the mRNA targets, causing a decrease in mRNA target expression. The poor correlation between cold-affected miRNAs and mRNAs observed previously [30] might be due to the time of sample collection or the use of different tissues (brain tissue vs. whole larvae used here). The duration of stress also determines if cells can re-establish homeostasis or initiate the mechanism to acclimate to the new environment [57].…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Several previous studies have analyzed global microRNA expression in zebrafish embryos using microarrays (Thatcher et al, 2007; Zhang et al, 2011; Tal et al, 2012; Wu et al, 2012) and deep sequencing (Soares et al, 2009; Cifuentes et al, 2010; Yang et al, 2011; Wei et al, 2012). Some of these studies have also used real-time RT-PCR to confirm their results.…”
Section: Discussionmentioning
confidence: 99%